2013
DOI: 10.1093/ndt/gft302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss on renal function in obese CKD patients: a systematic review

Abstract: Obesity is an independent risk factor for the development and progression of chronic kidney disease (CKD). We conducted a systematic review to assess the benefits of intentional weight loss in obese subjects with altered glomerular filtration rate (GFR), proteinuria or albuminuria. MEDLINE, EMBASE and CENTRAL databases were searched for articles reporting longitudinal data on the effect of weight loss on renal parameters in obese patients with altered kidney function. Thirty-one (2013 subjects) were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(135 citation statements)
references
References 53 publications
2
127
1
5
Order By: Relevance
“…Previous studies showed that obesity increased renal blood flow and also eGFR (12,13). The hyperfiltration in obese patients may result in renal dysfunction later on.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that obesity increased renal blood flow and also eGFR (12,13). The hyperfiltration in obese patients may result in renal dysfunction later on.…”
Section: Discussionmentioning
confidence: 97%
“…Campaigns aiming at reducing the obesity burden are now at center stage worldwide and are strongly recommended by the WHO and it is expected that these campaigns will reduce the incidence of obesityrelated complications, including CKD. However obesityrelated goals in obese CKD patients remain vaguely formulated, largely because of the paucity of high-level evidence intervention studies to modify obesity in CKD patients [81].…”
Section: Countering Ckd At Population Levelmentioning
confidence: 99%
“…No safety concerns regarding kidney-related adverse events were seen [83]. In a recent meta-analysis collating experimental studies in obese CKD patients, interventions aimed at reducing body weight showed coherent reductions in blood pressure, glomerular hyperfiltration and proteinuria [81]. A thorough post-hoc analysis of the REIN study showed that the nephron-protective effect of ACE inhibition in proteinuric CKD patients was maximal in obese CKD patients, but minimal in CKD patients with normal or low BMI [84].…”
Section: Prevention Of Ckd Progression In Obese People With Ckdmentioning
confidence: 99%
“…No safety concerns regarding kidney-related adverse events were seen [83]. In a recent metaanalysis collating experimental studies in obese CKD patients, interventions aimed at reducing body weight showed coherent reductions in BP, glomerular hyper-filtration and proteinuria [81]. A thorough post hoc analysis of the REIN study showed that the nephron-protective effect of ACE inhibition in proteinuric CKD patients was maximal in obese CKD patients, but minimal in CKD patients with normal or low BMI [84].…”
Section: Prevention Of Ckd Progression In Obese People With Ckdmentioning
confidence: 99%